Strategi Jalur-Ganda dalam Pemajuan Pertanian Indonesia: Memfasilitasi Generasi Milenial dan Menyejahterakan Petani Kecil - Benyamin Lakitan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Lakitan B. 2019. Double track strategy for agriculture development in indonesia: facilitating millennial generation and improving livelihood of smallholder farmers. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 1-8. Palembang: Unsri Press.Agricultural development in Indonesia has not been able to solve two main fundamental problems. Firstly, advancement of agricultural technology failed to significantly improve livelihood of smallholder farmers; instead, it creates wider gap between developed technology and farmer’s adoption capacity. Secondly, educated young generation who has capacity to employ sophisticated technologies has not interested to work in agriculture sector. In 2018, there were 38.7 million farmers in Indonesia, where as 88.27 percent of them were categorized as informal workers. This number was about one third of total Indonesian workers. They could be time bombs if they are not treated wisely. Their livelihoods should be appropriately improved. The efforts require availability of relevant, affordable, and profitable agricultural technologies. Meanwhile, at present, only few of the millennials interested to work in agriculture sector. This small group of millennial farmers should be encouraged to stay in agriculture, in order to motivate more young generation to follow them. Urban and peri-urban agriculture based on relevant technologies seems to fit well with millennial farmers.Keywords: agricultural development, millennial farmers, welfare of farmers, urban agriculture